Sequence Learning Under Uncertainty in Children: Self-Reflection vs. Self-Assertion - Lange-Küttner, Christiane; Averbeck, Bruno B.; Hirsch, Silvia V.; Wießner, Isabel; Lamba, Nishta (Frontiers in Psychology, 2012)
We know that stochastic feedback impairs children’s associative stimulus-response (S-R) learning (Crone, Jennigs, & Van der Molen, 2004a; Eppinger, Mock, & Kray, 2009), but the impact of stochastic feedback on sequence learning that involves deductive reasoning has not been not tested so far. In the current study, 8- to 11-year-old children (N = 171) learned a sequence of four left and right button presses, LLRR, RRLL, LRLR, RLRL, LRRL and RLLR, that needed to be deduced from feedback because no directional cues were given. One group of children experienced consistent feedback only (deterministic feedback, 100% correct). In this condition, green feedback on the screen indicated that the children had been right when they were right, and red feedback indicated that the children had been wrong when they were wrong. Another group of children experienced inconsistent feedback (stochastic feedback, 85% correct, 15% false), where in some trials, green feedback on the screen could signal that children were right when in fact they were wrong, and red feedback could indicate that they were wrong when in fact they had been right. Independently of age, children’s sequence learning in the stochastic condition was initially much lower than in the deterministic condition, but increased gradually and improved with practice. Responses towards positive vs. negative feedback varied with age. Children were increasingly able to understand that they could have been wrong when feedback indicated they were right (self-reflection), but they remained unable to understand that they could have been right when feedback indicated they were wrong (self-assertion).